Pengembangan Penuntun Praktikum Biologi Berbasis Pendekatan Saintifik untuk MTS/SMP Kelas VII Semester II - Sumarmin, Ramadhan; Roza, Rizka Khairia (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2019)
The main problem in the Junior High School of West Rengat is the absence of biology laboratory work guide for the practical activities. The presentation of the biology laboratory work guide in the student work sheets, and text books is still in a cookery model. It is not optimal to support student?s skill in science process. The aimed of this research to produce a valid, practical and efffective biology practical guide based on scientific approach for student at class VII of MTs/SMP in 2nd semester. The research used the Plomp model that has the preliminary research, the prototype phase and assessment phase. The data collect used validator sheet, practicalities by teacher and students questionnaires, observations of student activity sheets, student motivation questionnaire, and the paper-pencil test to cognitive student competence. The data were analyzed with the description of the percentage. The results showed that the biology laboratory work guide based on scientific approach for student at class VII of MTs/SMP in 2nd semester have validation score 83,05% (very valid category), the practicalities score 87,56%  (very practice), and effectiveness score 84,36% (very effective). It can conclude that the biology laboratory work-guide based on scientific approach for student at class VII of MTs/SMP in 2nd semester has very valid, practical, and effective.